STRATEGI GURU DALAM MENUMBUHKAN MINAT BACA PADA SISWA KELAS 1 DI SDN 4 KERTASARI - Fitriani, Fitri; Hidayat, Yusuf; Sugiarti, Sri (Jurnal Intisabi, 2025)
Reading interest is a key component to develop literacy skills, especially for first-grade elementary students to begin their learning journey. This study aims to explore the reading interest of first-grade students at SDN 4 Kertasari, the strategies used by teachers to enhance it, and the impact of those strategies. The study employed a qualitative method under a case study approach. The results of the study revealed that there is a positive improvement on students' reading interest, as shown through enthusiastic expressions, high curiosity, strong focus during reading, and feelings of satisfaction. Afterwards, the teacher’s strategies included: (1) daily 15 minutes reading habits; (2) providing a comfortable reading corner; (3) displaying illustrated motivational words; and (4) offering colorful, engaging books. This strategy has a positive impact on reading comprehension, reading fluency, letter recognition, and receiving feedback from parents towards the teacher’s success in increasing their children’s reading interest.